Recent trends in membranes and membrane processes for desalination - Goh, P. S. (Elsevier B.V., 2016)
Access to clean water resource continues to be the most urgent and pressing global issue where hiking economic and ecological needs have urged for more water-efficient technologies. Membrane-based separations for desalination are playing an increasingly important role to provide adequate water resources of desirable quality for a wide spectrum of designated applications. The engagement of multidisciplinary research areas into the commercial membrane and membrane systems offers an opportunity to refine and optimise current techniques as well as provides new insight and novel methods of purifying water. The advancement of material science and engineering reveals the potentials to solve real-world practical problems and heighten the current technologies. This review highlights some of the latest notable achievements of novel advanced membrane materials and emerging membrane processes for water solution. The unique characteristics of advanced membranes and emerging membrane processes in leading the state-of-the-art desalination are presented. Lastly, the future directions for research, development and commercialization of membrane and membrane processes are critically discussed. It is expected that, the promising and well-adapted characteristics possessed by the novel membranes and advanced membrane processes can provide meaningful inspiration for breakthrough technologies and solutions where soon they will be translated into exploitable innovations in industries.